PEMBAYARAN E-PAYMENT SERTA PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN DI E-COMMERCE - Sudung Simatupang ,; Ernest Grace ,; Christine Dewi Nainggolan ,; Nelly Ervina , (Journal of Innovation Research and Knowledge, 2024)
Nowadays, e-payment is one of the most attractive payment models for consumers in making purchases, especially with purchases made through e-commerce. The purpose of this study was to look at the e-payment system on purchasing decisions through e-commerce. The results of data analysis show that the instruments of the research variables e-payment and purchasing decisions show valid and reliable results. The value for the coefficient of determination of the research results shows the ability of the e-payment variable to explain purchasing decisions is 61%, while the rest is a variable that is not discussed in this study. The results of the regression equation Y = 7, 498 + 0.748X, this shows a positive direction coefficient value of e-payment on purchasing decisions, and the hypothesis results show positive and significant results from e-payment on purchasing decisions in e-commerce. which means that the more people use the E-Payment method, the more likely consumers are to decide to make purchases in E-commerce